Training in Open Dialogue and Dialogical Practice: creatively responding as trainers and writers - Thorley, Catherine; Brown, Judith M.; Kurtti, Mia; Taylor, Alita (Frontiers in Psychology, 2023)
This paper emerges from a series of conversations about training in Open Dialogue and dialogical practice. In our dialogue, we found ourselves moving away from seeking definitive answers about content (what to include) or process (how to include). We asked, “Why are we asking this question about training at all?” Maybe it is because many helpers and all kinds of professionals all over the world are truly asking, “How do we do, or how do we learn how to do ‘open dialogue’?.” That question starts with “How to train others in the practice?” We moved toward responding to our own questions—what are we offering as trainers and what are the trainees seeking? We sought to explore what is required for a training space that accommodates the hopes of both trainers and trainees. Words arose during our talking, and we listened to them, let them sink in, and reflected on them. Some words resonated with us as trainers; some linked with observing trainees’ experiences (including our own); some showed a glimpse of the relationship between trainer and trainees. These emergent words point to a series of learnings, aspects of the training that we as trainers have come to believe are important. The following paper expands upon these words while also including actual portions of our dialogues and vignettes from training. As such, we illustrate our ongoing learning as trainers of Open Dialogue and dialogical practice as it occurs within the unique nature of each training we provide.